General aspects about the object in the Tadeusz Kantor Theater (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
Tadeusz Kantor (Wielopole/Poland – 1915-1990) was one of the most important theater men of the 20th century. Kantor’s theater has an intense connection with the visual arts and was greatly influenced by the avant-gardes of the first half of the last century. The Kantorian theater has several supporting elements; however, the object, whether taken from everyday reality or constructed exclusively for a scenic purpose, permeates his entire work. Thus, this article seeks to make some notes about the object in Tadeusz Kantor’s theater to enable a better understanding of the existence on stage as an aesthetic object and also as a conceptual object.
Keywords: Kantor; object; theater; Visual arts